The Preparation of C-S-H Powder Seeds and Their Effect on the Early Hydration Performance of Cement Paste - Chunlong Huang; Yiren Wang; Zhongyuan Wei; Yong Yu (Crystals)
C-S-H/PCE suspension can boost the hydration degree and strength of cement composite binding. However, the suspension will inevitably precipitate after a period of time, which is not conducive to its preservation, and its low solid content increases transportation costs in practical applications. In this study, utilizing synthetic PCE as a template, C-S-H/PCE suspension was synthesized using a co-precipitation method. Subsequently, powder seeds were produced via the spray-drying technique, and these prepared powder seeds were analyzed via microscopic characterization. The impact of these powder nucleating agents on cement hydration kinetics was evaluated through hydration heat measurements and hydration degree, fluidity, and compressive strength testing. The results indicated that these powder seeds exhibited a nano-film morphology. Their nucleation effect significantly enhanced the cement hydration rate, increased the degree of hydration, and improved strength. The hydration kinetics showed that the hydration of cement mixed with nucleating agents was not governed by a single reaction mechanism, but rather constitutes a complex, multi-component reaction process. As the content of nucleating agents increased, higher dosages of nucleating agents accelerated the production of more products within a short period, causing the system to rapidly transition to phase boundary reaction control. When the dosage of nucleating agents reached 2%, the cement hydration process bypassed the phase boundary reaction control stage and transitioned directly from the crystallization nucleation and crystal growth control process to the diffusion-controlled phase. Although the influence of powder seeds on the enhancement of the early-stage strength of mortar was slightly lower than that of the suspension, the powder was beneficial to its storage and transportation. Therefore, it has the potential to replace the suspension.